Strategic Use of Academic Databases across the Research Lifecycle: A Framework for Universities and Research Institutions - Hussain, Arshad; Bhati, Dolly (Information Research Communications, 2026)
Background Academic databases are very important tools for research at universities and research institutions. Researchers use academic databases to retrieve literature, check citations, and assess research activity. However, there are differences between various databases in terms of scope, availability, subject area, and citation index. ### Problem Statement/Gap in Literature While existing studies have usually based their comparison on the scope and citation indicators of academic databases, they do not reflect the use of these databases in the various stages of the research process. Methodology In this research note, the major academic databases namely Scopus, Web of Science, Google Scholar, PubMed, Dimensions and OpenAlex are compared with each other and with other studies. In addition, a new model is introduced that takes into account the comparison of the suitability of academic databases for research based on purpose, discipline and access factors. Results The results indicate that Scopus and Web of Science are recommended for citation analysis and research assessment, while Google Scholar is useful for literature searches and PubMed remain a key database for medical research. Conclusion The purpose of this research note is to provide a number of recommendations to researchers and organizations for the selection and use of academic databases at various stages of research activities.
Keywords: Academic databases; Scopus; Web of Science; Google Scholar; PubMed; Bibliographic databases; Research lifecycle.